Endothelial C-Type Natriuretic Peptide Acts on Pericytes to Regulate Microcirculatory Flow and Blood Pressure. Issue 5 (31st July 2018) - Špiranec, Katarina; Chen, Wen; Werner, Franziska; Nikolaev, Viacheslav O.; Naruke, Takashi; Koch, Franziska; Werner, Andrea; Eder-Negrin, Petra; Diéguez-Hurtado, Rodrigo; Adams, Ralf H.; Baba, Hideo A.; Schmidt, Hannes; et al.
Abstract : Background: Peripheral vascular resistance has a major impact on arterial blood pressure levels. Endothelial C-type natriuretic peptide (CNP) participates in the local regulation of vascular tone, but the target cells remain controversial. The cGMP-producing guanylyl cyclase–B (GC-B) receptor for CNP is expressed in vascular smooth muscle cells (SMCs). However, whereas endothelial cell–specific CNP knockout mice are hypertensive, mice with deletion of GC-B in vascular SMCs have unaltered blood pressure. Methods: We analyzed whether the vasodilating response to CNP changes along the vascular tree, ie, whether the GC-B receptor is expressed in microvascular types of cells. Mice with a floxed GC-B ( Npr2 ) gene were interbred with Tie2-Cre or PDGF-Rβ-Cre ERT2 lines to develop mice lacking GC-B in endothelial cells or in precapillary arteriolar SMCs and capillary pericytes. Intravital microscopy, invasive and noninvasive hemodynamics, fluorescence energy transfer studies of pericyte cAMP levels in situ, and renal physiology were combined to dissect whether and how CNP/GC-B/cGMP signaling modulates microcirculatory tone and blood pressure. Results: Intravital microscopy studies revealed that the vasodilatatory effect of CNP increases toward small-diameter arterioles and capillaries. CNP consistently did not prevent endothelin-1–induced acute constrictions of proximal arterioles, but fully reversed endothelin effects in precapillary arterioles and capillaries. Here, the GC-B receptor is expressed both in endothelial and mural cells, ie, in pericytes. It is notable that the vasodilatatory effects of CNP were preserved in mice with endothelial GC-B deletion, but abolished in mice lacking GC-B in microcirculatory SMCs and pericytes. CNP, via GC-B/cGMP signaling, modulates 2 signaling cascades in pericytes: it activates cGMP-dependent protein kinase I to phosphorylate downstream targets such as the cytoskeleton-associated vasodilator-activated phosphoprotein, and it inhibits phosphodiesterase 3A, thereby enhancing pericyte cAMP levels. These pathways ultimately prevent endothelin-induced increases of pericyte calcium levels and pericyte contraction. Mice with deletion of GC-B in microcirculatory SMCs and pericytes have elevated peripheral resistance and chronic arterial hypertension without a change in renal function. Conclusions: Our studies indicate that endothelial CNP regulates distal arteriolar and capillary blood flow. CNP-induced GC-B/cGMP signaling in microvascular SMCs and pericytes is essential for the maintenance of normal microvascular resistance and blood pressure. Abstract : Supplemental Digital Content is available in the text.